Severe salicylate poisoning resistant to conventional management. Issue 6 (2nd November 2018) - Akshintala, Divya; Mendez, Anjeanette; Ikladios, Ossama I.; Emani, Vamsi Krishna
ABSTRACT: Aspirin remains one of the most common agents involved in both accidental and intentional overdose. The availability of enhanced elimination and early hemodialysis has been known to reduce the number of deaths from salicylate poisoning. We present the case of an intentional aspirin overdose with enteric-coated preparation that had continuously rising salicylate levels despite treatment with bicarbonate drip, continuous dialysis and activated charcoal.